NARASI VISUAL DISKURSUS TUBUH PADA KARYA DIGITAL PAINTING DALAM TINJAUAN BUDAYA (STUDI KASUS KARYA MASSIVE WAR â AGAINST SAD RIPU) - Yusa, I Made Marthana; Triyadi, Agus (LPPM BSI Bandung, 2014)
Abstract - Body discourse often implemented and visualized into art and design artform. This article reveals designing process with digital painting tehnique which narrate body discourse in term of cultural observation. The artwwork object entitled : Massive War â Against Sad Ripu. Methodology started with methodological phases to reveal the visual narration and conceptual meaning consisted. The next phase is to reveal the concept art connected with body discourse and phenomena about the ways human respond its issue visualized into artwork in cultural point of view. The cultural observation measured up to Eastern socio culture (Buddhisme-Hinduisme). The output of the observation reveals spesific values that narrates in visual way related to body discourse in scope of cultural observation.Â Keywords : Visual Narration, Body Discourse, Multiculturalism, Massive, War, Sad Ripu, Hinduisme, BuddhismeÂ Abstrak - Diskursus terhadap tubuh seringkali divisualisasikan dalam wujud karya seni rupa dan desain. Pada artikel ilmiah ini diungkap proses penciptaan karya dengan teknik digital painting. Karya tersebut berjudul Massive War-Against Sad Ripu oleh I Made Marthana Yusa. Metodologi diawali dengan langkah-langkah metodologis mengungkap pesan dan narasi visual yang terkandung pada ilustrasi. Langkah selanjutnya mengungkap konsep karya yang berhubungan dengan diskursus tubuh dan bagaimana manusia merespon diskursus tubuh dalam visualisasinya pada karya dari sudut pandang budaya. Tinjauan budaya dibatasi pada socio-culture Timur (Buddhisme-Hinduisme). Hasil kajian mengungkap nilai-nilai khusus yang dinarasikan secara visual berdasar atas diskursus tubuh dalam batasan tinjauan budaya.Â Kata Kunci : Narasi Visual, Diskursus Tubuh, Multikulturalisme, Sad Ripu, Hinduisme, Buddhisme